A compact inverted Y‐shaped circularly polarized wideband monopole antenna with open loop. Issue 5 (15th November 2020) - Dhara, Reshmi; Kundu, Taraknath
Abstract: This article presents a novel, compact, single feed circularly polarized (CP) microstrip antenna. Proposed design involve an inverted Y‐shaped radiating patch fed by an L‐shaped microstrip line feed and a rectangular open‐loop placed near its right corner. A semi‐rectangular ground plane is used on the opposite side of the substrate. Coupling between the rectangular open‐loop and the inverted Y‐shaped patch plays a vital role in attaining wideband CP, while the semi‐rectangular ground plane is crucial for enhancing impedance bandwidth (IBW). The optimized design achieved measured wide IBW of 5.164 GHz (65.53%, spanning over 5.297‐10.461 GHz) having its center frequency ( f rc ) at 7.878 GHz. The corresponding measured axial ratio bandwidth (ARBW) obtained inside the measured IBW curve is 2.25 GHz (having its center CP resonating frequency f cp 7.52 GHz, spanning over 6.40‐8.65 GHz, 29.92%). Measurement results are validated in both Ansys Electronics Desktop 2020 R1 and CST Microwave Studio 2018. Proposed antenna is fabricated on FR‐4 epoxy substrate of 1.6 mm thickness and exhibits a very small footprint of just 400 mm 2 (20 × 20 mm 2 ) (size 0.58 λ mgL × 0.58 λ mgL × 0.046 λ mgL, where λ mgL is the measured guided wavelength at lower resonating frequency f mrL = 5.297 GHz) with 51.31% reduction in size. Measured maximum peak gain for the impedance band is 2.04 dBi at 8.8 GHz and 1.96 dBi at f cp 7.52 GHz. The structure of the proposed antenna is extremely simple, quite small in size and its CP bands can be suitable for some C‐band and ITU (International Telecommunication Union)—8 GHz application. Abstract : Experimental setup used for the proposed antenna: (A) and (B) reflection coefficient measurement.